Anisotropy in spatial summation properties of human Ocular-Following Response (OFR) - Sheliga, B. M. (Vision Res, 2015)
Using sinusoidal gratings we show that an increase in stimulus size confined to the dimension orthogonal to the axis of motion leads to stronger Ocular Following Responses (OFRs) up to a certain optimal size. An increase beyond this optimum produces smaller responses, indicating suppressive interactions. In sharp contrast, when the stimulus growth occurs parallel to the axis of motion OFR magnitudes increase monotonically both for horizontal and vertical directions of motion. Similar results are obtained with 1D white noise patterns. However, the OFR spatial anisotropy is minimal with 2D white noise patterns, revealing a pivotal role of orientation-selective (i.e., cortical) mechanisms in mediating this phenomenon. The lack of anisotropy for 2D patterns suggests that directional signals alone are not sufficient to elicit this suppression. The OFR spatial anisotropy is potentiated if a stationary grating is presented for 600-1000 ms before its motion commences, further emphasizing the importance of static orientation signals. These results suggest that the strength of cortical spatial interactions is asymmetric—i.e., larger in the direction of the ends than the flanks of an orientation-selective receptive field—which corroborates the existing neurophysiological evidence.